Short explanation of hybrid cantang grouper (Epinephelus lanceolatus x Epinephelus fuscoguttatus) - Muh. Sulaiman Dadiono; Aminin Aminin (PT. Gyandharma Global Media, 2025)
Hybrid cantang grouper is the result of cross-breeding engineering between the Epinephelus lanceolatus and Epinephelus fuscoguttatus grouper species. This hybrid grouper was first developed by BPAP Situbondo under the auspices of the Ministry of Marine Affairs and Fisheries of the Republic of Indonesia. This article briefly explains the hybrid cantang grouper starting from morphology, habitat, reproductive cycle and cross-breeding methods.